PENERAPAN TEKNOLOGI TEPAT GUNA BERUPA MESIN PEMIPIL JAGUNG DAN STRATEGI PEMASARAN YANG EFEKTIF UNTUK MENINGKATKAN PENDAPATAN KELOMPOK TANI SITAMBIRI - Muhammad Ilham Maulana; Wesly Mailander Siagian; Debora Indrawarsi Manullang; Octaviana Simanjuntak; Rizal Horas Manahan Sinaga (Universitas Mataram, 2026)
A community service program (PkM) was carried out with the aim of applying appropriate technology in the form of a corn sheller machine and strengthening the marketing capacity of harvested products through education on distribution strategies and product packaging for the Sitambiri Farmers Group. Corn is recognized as a strategic commodity suitable for cultivation in dryland areas. From the demand side, corn serves as a primary raw material in the animal feed industry, making its price relatively stable and tending to increase. The Sitambiri Farmers Group, consisting of 15 members in Lumban Dolok Village, Silaen District, Toba Regency, chose to cultivate corn as an effort to increase income. However, the use of conventional corn shellers remains a challenge due to inefficiency in time and labor, as well as poor ergonomics for farmers. This PkM activity aims to improve efficiency and production quality through the application of appropriate technology in the form of a corn sheller machine. In addition, the program provides education on marketing strategies, opens opportunities for product diversification, and encourages the improvement of farmers’ welfare. The method applied in this activity was the design of a corn sheller machine using the Axiomatic House of Quality (AHOQ). The second stage of the program focused on marketing management strategies through Focus Group Discussions (FGD) with members of the farmers group. The implementation of the corn sheller machine significantly increased capacity, reaching 17 kg per minute. The machine is more ergonomic as it reduces farmers’ workload, produces more uniform kernels with less product loss, and generates positive economic impacts. In the second-stage FGD, partners actively participated in discussions on distribution strategies, market segmentation, and the potential development of processed corn products. Active participation of the farmers group in discussions and simulations demonstrated an increase in their capacity to design marketing strategies suited to local conditions, such as online store marketing. Thus, the corn sheller machine improves efficiency and production quality, while marketing strategies strengthen the capacity and competitiveness of the farmers group.